Identificación de parásitos gastrointestinales y factores asociados en cabras de la parroquia Garzareal, cantón Zapotillo de la provincia de Loja - Yaguachi Ochoa, Jennifer Andrea (2024)
In Zapotillo canton the goat farming are mostly managed by small livestock producers and it is mainly characterized by extensive farming, with poor health management. Gastrointestinal parasites are an animal health issue that affects the local population as it has an impact in the capriculturist economy. The objective of the research was to identify gastrointestinal parasites and factors associated with their presence in goats from the Garzareal parish of the Zapotillo canton in Loja province. Sampling was carried out on 20 farms where 100 samples of goat feces were obtained to be subjected to qualitative tests (flotation technique and direct smear method). A 55% presence of gastrointestinal parasites was obtained, in the flotation technique the genus Trichostrongylus stands out with 24% and in the direct smear method Ascaris with 28%, being the most predominant. The work also addressed associated factors where a survey was applied to capriculturists; which involved investigating environmental conditions, management practices and other elements that influenced the identification of gastrointestinal parasites, of which sex, age, and diet were involved, and may be related to the presence of gastrointestinal parasites. This information was of great importance to understand the dynamics of parasitic infections in goats in the studied area. The results obtained important implications for farmers and ranchers in the region, which provided relevant data for the design of parasite management and control strategies. The study contributes to scientific knowledge on the epidemiology of gastrointestinal parasites in specific populations of goats, with possible implications for animal health and livestock production.